Comparative Analysis of the Financial Performance of Islamic and Conventional Banking Before and During the Covid-19 Pandemic - chia chia putri milennia; Hendri Andi Mesta (Financial Management Studies, 2022)
The final goal to be achieved in this study is to find out whether there are differences in the financial performance of Islamic and conventional banking before the pandemic and during the pandemic by using the Independent sample t-test in analyzing the Capital Ratio (CAR), Asset Quality Ratio (NPF/NPL), Profitability Ratio (ROA), Liquidity Ratio (FDR/LDR) and Efficiency Ratio (BOPO). The object of research is sharia and conventional banking registered with OJK as a National Private Commercial Bank. The sample selection in this study used a purpose sampling technique and the data used in this study is secondary data obtained from the OJK websitewww.ojk.go.id.The results of the Independent sample t-test showed that before the pandemic (2018-2019), there were significant differences in CAR and ROA in Islamic and conventional banking, and there were no significant differences in NPF/NPL, FDR/LDR, BOPO in Islamic banking. and conventional. Meanwhile, during the pandemic (2020-2021) there are significant differences in ROA and FDR/LDR for Islamic banking and conventional banking, while there are no significant differences in CAR, NPF/NPL, BOPO for Islamic and conventional banking. In this study, it was found that the financial performance of Islamic banking before the pandemic was better than conventional banking, but during the NPL, LDR and BOPO pandemics, conventional banking was better, while Islamic banking was better in CAR and ROA.